PENGARUH PERUBAHAN TUTUPAN LAHAN TERHADAP KONDISI HIDROLOGIS KAWASAN DAERAH ALIRAN SUNGAI TALAU - Alfred Umbu K. Ngaji (Politeknik Pertanian Negeri Kupang, 2009)
The affect of landcover changes on regional hydrological conditions of Talau Watershed. Deforestation and landcover changes are influenced factors on global climate changes. NTT is one province in Indonesia which has dry climate conditions and susceptible to that changes. Talau watershed is one of some watershed in NTT which has a dry area with only three wet months in a year. A hydrological model (Gen River) is used to study and estimate water balance in the watershed. Land use, rainfall, soil, DEM and drainage characteristics are the main input components of the model. Some plausible scenarios were simulated using this model. Landcover changes in this area were studied using spatial analysis. Satellite imageries were analyzed using object based techniques to produce landcover maps of 1989 to 1999. Land classification scheme categorized forest, agroforest, plantation, agriculture, grass, rice field, settlement, clear land and water body. To analyzed vegetation index, Normalized Difference Vegetation Index (NDVI) was used as one of the variables to separate forest, tree based systems, non tree based systems and non vegetation. Besides tasseled-cap transformation wasÂ used to interpret more detailed vegetation type differences. The landcover changes pattern showed that during the ten years period forest conversion toÂ Â tree based systemwas about 24 km (3%) and there was 15% increase of non-agricultural landcover, such as grass and bare land. As an input to GenRiver, the landcover classes were reclassified as forest, tree based systems, agriculture and non-agricultural systems. Conversion of 105 km non agricultural systems to tree-based resulted in the decrease of run-off from 43% to 64% and decreasing run-off from 78% to 90% as forest. Decrease of tree landcover can increase soil flow from 1% to 7% from totally rainfall. The land cover changes did not affect for soil quick flow, but it can decrease erosion and flood in wet season. Keywords: dry land, landcover changes, hydrological modeling